FGD1 Variant Associated With Aarskog–Scott Syndrome - Zhu, Yilin; Chen, Qingqing; Lin, Haiyan; Lu, Huifei; Qu, Yangbin; Yan, Qingfeng; Wang, Chunlin (Frontiers in Pediatrics, 2022)
Background: Aarskog-Scott syndrome, a relatively rare X-linked genetic disease, is diagnosed by clinical combination of facial, skeletal and genital anomalies. It is estimated that two to three new cases are diagnosed annually with confirmed by genetic testing. FGD1, the only one gene that is identified to be associated with Aarskog-Scott syndrome. There is no specifictherapy for Aarskog-Scott syndrome due to the unknown mechanisms. Methods: Clinical data were collected at the time of patient visit. Clinical Trio-WES testing and Sanger sequencing were performed for the unbiased search for the genetic cause of disease. To evaluate the pathogenicity of the variants in vitro, stable cell lines were constructed using lentivirus transduction. Furthermore, Western blotting were used to check the expression of signaling pathway-related proteins and the transcript levels of osteogenic-related genes, including OCN, COL1A1 was checked by luciferase reporter gene assays. Results: A 7-year-old boy was manifested with facial abnormalities, intellectual disability, and short stature (-3.98SDS) while the growth hormone level of stimulation tests were normal. Trio-WES and Sanger sequencing identified a variant, c.1270A>G (r.1270a>g, p. Asn424Asp) in FGD1 gene. The Asn424 residue was highly conserved and the hydrogen bonds in the FGD1 variant protein has changed, which led to decrease of the interaction with CDC42 protein. In vitro studies showed that the Asn424Asp variant significantly decreased the expression of OCN, COL1A1 and ALP, and activated the phosphorylation of JNK1. Conclusion: Molecular biological mechanisms underlying abnormal expression of FGD1 gene and Aarskog-Scott syndrome remains poorly understood. In our studies, Asn424Asp variant of FGD1 gene resulted in Aarskog-Scott syndrome and the analysis of pathogenicity support the deleterious effect of the variant. Furthermore, we have demonstrated the variant weakened the interaction with CDC42 and decrease the expression of osteogenic-related gene through abnormal activation of JNK1 in vitro.